2023
DOI: 10.1021/acs.jpclett.3c02042
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Antibacterial Nanoplatform Bi2WO6:Nd3+/Yb3+/Er3+@MoS2 with Self-Monitoring Photothermal and Photodynamic Treatment

Minkun Jin,
Jinmeng Xiang,
Changheng Chen
et al.

Abstract: Synergistic therapy combining photothermal therapy and photodynamic therapy is considered to be a promising approach to treat cancer, but the precise temperature control of deep tissue remains a great challenge in achieving effective treatment. Herein, a two-dimensional Bi2WO6:Nd3+/Yb3+/Er3+@MoS2 nanoplatform with photothermal and photodynamic functions was constructed, where semiconductor MoS2 serves as both a photothermal agent and a photosensitizer. The photothermal conversion performance and the reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, the maximum Sr obtained from NTCLs of the Er 3+ /Tm 3+ ion is less than that obtained from TCLs in NSYM: Er 3+ /Tm 3+ /Yb 3+ . These bands are significant because they are situated in the first biological window spectral area, which is ideal for biological systems’ need for temperature sensing. …”
Section: Resultsmentioning
confidence: 99%
“…However, the maximum Sr obtained from NTCLs of the Er 3+ /Tm 3+ ion is less than that obtained from TCLs in NSYM: Er 3+ /Tm 3+ /Yb 3+ . These bands are significant because they are situated in the first biological window spectral area, which is ideal for biological systems’ need for temperature sensing. …”
Section: Resultsmentioning
confidence: 99%
“…In order to further check the performance of the temperature sensor, the temperature resolution (δ T ) is calculated. Through the following formula: 63,64 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the experiment was repeated for ten cycles under the same measurement conditions and quantified by the following formula. 63,64 where LIR m and LIR a represent the mean value of the intensity ratio at each temperature and the actual measurement results, respectively. In Table 3, the repeatability ( R ) of the three temperature measurement modes is greater than 95% at all temperatures, so it can be concluded that the temperature sensor has high repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…Chemiluminescence represents the emanation of light in a chemical reaction in which a molecule is thermally activated and experiences a nonadiabatic transition to an electronic excited state of the fragmentation product. The process is called bioluminescence when it occurs in living organisms, e.g., fireflies. Chemiluminescence or bioluminescence has wide-ranging applications, such as treating cancers via photodynamic therapy, acting as a bioluminescence imaging tool, , and tracking environmental pollutants . The thermolysis of the four-membered heterocyclic peroxides, e.g., 1,2-dioxetane, generates electronically excited state carbonyl compounds that emit light to release the excess energy (see Figure ).…”
mentioning
confidence: 99%